Efektifitas Pemberlakuan Keputusan Menteri Kelautan dan Perikanan Nomor 80 Tahun 2020 terhadap Penangkapan Glass Eel Sidat di Muara Sungai Cimandiri, Kecamatan Simpenan, Kabupaten Sukabumi: Penelitian - Aldi Hakim; Ine Maulina; Alexander Khan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Fisheries management policy regulations are a fundamental pillar in addressing the problem of fisheries resource utilization, including overfishing, by providing controlled limits for fishermen and the industry. This study aims to analyze glass eel catches in the Cimandiri River Estuary, Palabuhanratu, Sukabumi, West Java, after the implementation of Ministerial Decree No. 80 of 2020. This study was conducted in February - March 2025 using a survey method with a quantitative approach and descriptive analysis of the data. The determination of respondents was carried out using a purposive sampling technique with a total of 30 people. The results of the study indicate that this policy is not fully effective. Fisherman compliance is still low due to a lack of understanding, economic factors, and minimal supervision.